ChemInform Abstract: Catalytic Reduction of ortho‐ and para‐Azidonitrobenzenes via tert‐Butoxide Ion Mediated Electron Transfer. Issue 28 (21st June 2013) - Burnley, James; Carbone, Giorgio; Moses, John E.
Abstract The novel method employing tert‐butoxide as the reductant and a thiazolium salt as the catalyst allows the chemoselective reduction of an azide in the presence of a sensitive nitro group.